Estudo da dispersão larval radial pós-alimentar em Chrysomya megacephala (Fabricius) (Diptera, Calliphoridae) - Gomes,Leonardo (2003)
Blowflies utilize discrete and ephemeral sites for breeding and larval nutrition. After the exhaustion of food, the larvae begin dispersing to search for sites to pupate or to additional food source, process referred as postfeeding larval dispersal. Some of the most important aspects of this process were investigated in Chrysomya megacephala, utilizing a circular arena to permit the radial dispersion of larvae from the center. To determinate the localization of each pupa, the arena was split in 72 equal sectors from the center. For each pupa, distance from the center of arena, weight and depth were determined. Statistical tests were performed to verify the relation among weight, depth and distance of burying for pupation. It was verified that the larvae that disperse farther are those with higher weights. The majority of individuals reached the depth of burying for pupation between 7 and 18 cm. The study of this process of dispersion can be utilized in the estimation of postmortem interval (PMI) for human corpses in medico-criminal investigations.